Transforming Student Behavior through Internalization of Values Aesthetics-Ethics in Traditional Dance Learning Based on Local Wisdom at SMPN 4 Cepu - Kusmini, Kusmini; Hartono Hartono (Universitas Negeri Semarang, 2025)
This study aims to analyze the implementation of traditional dance learning based on local wisdom at SMPN 4 Cepu, with a focus on the process of internalizing aesthetic-ethical values and transforming student behavior through a contextual and experiential learning approach. This study uses a qualitative method with a case study approach, involving participatory observation, in-depth interviews with teachers and students, and analysis of learning documents to collect comprehensive data from the field. The results show that learning takes place in a planned and effective manner through direct practice strategies, teacher demonstrations, and continuous habituation, which successfully integrates mastery of dance movement techniques with a deep understanding of cultural backgrounds, symbolic meanings, and local values. Aesthetic values are internalized through appreciation of movement, rhythm, facial expressions, and the beauty of dance forms, while ethical values are embedded through disciplined practice, group work, mutual respect, and adherence to norms in the affective, cognit ive, and psychomotor domains; this triggers real behavioral transformations in the form of increased self-confidence, discipline, collaboration skills, and appreciation of cultural diversity both in the learning environment and in daily school life. In conclusion, this approach has a positive impact on the formation of local identity and character of students, with suggestions for strengthening school policies through the pro vision of supporting facilities, innovation of teacher teaching strategies, active student participation, and further research to explore long-term effectiveness.​